Metadata quality in digital repositories: Empirical results from the cross‐domain transfer of a quality assurance process. (12th March 2014) - Palavitsinis, Nikos; Manouselis, Nikos; Sanchez‐Alonso, Salvador
<x xml:space="preserve">Abstract</x> Metadata quality presents a challenge faced by many digital repositories. There is a variety of proposed quality assurance frameworks applied in repositories that are deployed in various contexts. Although studies report that there is an improvement of the quality of the metadata in many of the applications, the transfer of a successful approach from one application context to another has not been studied to a satisfactory extent. This article presents the empirical results of the application of a metadata quality assurance process that has been developed and successfully applied in an educational context (learning repositories) to 2 different application contexts to compare results with the previous application and assess its generalizability. More specifically, it reports results from the adaptation and application of this process in a library context (institutional repositories) and in a cultural context (digital cultural repositories). Initial empirical findings indicate that content providers seem to be gaining a better understanding of metadata when the proposed process is put in place and that the quality of the produced metadata records increases.